1989
DOI: 10.1515/jpme.1989.17.5.333
|View full text |Cite
|
Sign up to set email alerts
|

Short communications

Abstract: It has been suggested that meconium-stained amniotic fluid can be detected in the antepartum period by means of ultrasound, based on the following findings: (1) a diffuse echogenic pattern throughout the amniotic cavity, (2) a clear contrast between the amniotic fluid and the umbilical cord, and (3) layering in the more dependent areas. Reported is a case in which a similar picture was obtained in a third trimester, high-risk pregnancy, but representing vernix instead of meconium. We are aware of six cases, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Benacerraf et al stated that the ultrasound diagnosis of meconium stained amniotic fluid could be made if amniotic fluid appear diffuse echogenic pattern throughout the amniotic cavity and clear contrast between the amniotic fluid and umbilical vessels 2 . In another study of case reported with similar findings identified vernix rather than meconium although prenatally they were mistakenly diagnosed as meconium 3 prenatal USG were also found to be vernix during artificial and spontaneous rupture of membrane at delivery 1 like our study. The study in 1976 noted that on USG vernix appeared after 36 weeks causing cloudy appearance of amniotic fluid 4 similar to our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Benacerraf et al stated that the ultrasound diagnosis of meconium stained amniotic fluid could be made if amniotic fluid appear diffuse echogenic pattern throughout the amniotic cavity and clear contrast between the amniotic fluid and umbilical vessels 2 . In another study of case reported with similar findings identified vernix rather than meconium although prenatally they were mistakenly diagnosed as meconium 3 prenatal USG were also found to be vernix during artificial and spontaneous rupture of membrane at delivery 1 like our study. The study in 1976 noted that on USG vernix appeared after 36 weeks causing cloudy appearance of amniotic fluid 4 similar to our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Hyperechogenic AF is an uncommon finding that is commonly due to the presence of vernix, though in some cases, it is associated with the presence of meconium or blood creating a dilemma for management of these patients. [ 7 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Review by Sepúlveda and Quiroz indicated that the finding of hyperechoic AF refers more often to a considerable amount of vernix rather than meconium. [ 10 ] However, they suggested amniocentesis or amnioscopy to rule out the presence of meconium. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benacerraf et al stated that the ultrasound criteria for diagnosis of meconium-stained amniotic fluid include (1) a diffuse echogenic pattern throughout the amniotic cavity, (2) a clear contrast between the amniotic fluid and the umbilical vessels, and (3) layering in the more dependent areas [9] . When echogenic amniotic fluid is identified in a third trimester obstetrical ultrasound, Sepulveda et al recommended direct visualization of the amniotic fluid by amniocentesis or amnioscopy, or a careful study of the fetal well-being by means of nonstress test, and/or biophysical profile [10] as fetal distress or cord compression may result in passage of meconium stool [11] . However, non-passage of meconium can be attributed to small size of internal opening of VF, the physics underlying Bernoulli’s theorem or the Venturi effect, thick viscosity of meconium, and poor intestinal peristalsis in fetus.…”
Section: Discussionmentioning
confidence: 99%